Energy harvesting approach for trackside health monitoring devices in railroads. Issue 1 (20th September 2021) - Zhang, Jimin; Xu, Lichao; Shen, Tuo; Luo, Jinnan
Abstract: Design, modelling, simulation and lab test of a trackside electromagnetic energy harvesting (TEEH) approach for an AC electrified railway is provided in this study. By collecting the electromagnetic energy inspired from track current, an alternative energy source along the trackside can be achieved, which is not sensitive to weather and location factors. This study aims to verify the feasibility of TEEH and provide a guideline for future study. The electromagnetic field distribution model of the rail is built through theoretical calculations and FEM simulation. The relationship between harvester parameters and output power is confirmed. A TEEH prototype test bench has been built to verify the theory. The result indicates a close match. The average output power of 9.2 mW is achieved from a Φ57 × 30 mm hollow coil when the track current is 600 A 50 Hz. This study proposed a detailed derivation and modelling process, providing a preliminary reference and guidance for the design of an electromagnetic energy harvester.